2018
DOI: 10.1080/25785826.2018.1531186
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism in rheumatoid arthritis

Abstract: Recent studies have revealed a relationship between cellular metabolism and cell function in immune cells. Cellular metabolism not only provides supplemental ATP, but also supports dynamic changes in cell proliferation and differentiation. For example, T cells exhibit subsetspecific metabolic profiles, and require certain types of metabolism for their functions. Determining the metabolic profiles that support inflammatory immune responses may lead to novel treatment strategies for chronic inflammatory diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Some metabolic pathways, such as the glycolysis pathway, are important in maintaining this inflammatory state, as studies showed that metabolites of the glycolysis pathway were increased in the serum of RA patients [ 116 ], suggesting that changes in metabolism are associated with joint inflammation. A number of treatment interventions that modulate metabolism have been shown to have a therapeutic effect in RA (reviewed in [ 117 ]), a prime example of which is methotrexate (MTX). MTX has been used as a successful mono- or combination treatment to alleviate chronic symptoms in CHIKV patients [ 17 , 118 120 ] including a randomized controlled trial [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some metabolic pathways, such as the glycolysis pathway, are important in maintaining this inflammatory state, as studies showed that metabolites of the glycolysis pathway were increased in the serum of RA patients [ 116 ], suggesting that changes in metabolism are associated with joint inflammation. A number of treatment interventions that modulate metabolism have been shown to have a therapeutic effect in RA (reviewed in [ 117 ]), a prime example of which is methotrexate (MTX). MTX has been used as a successful mono- or combination treatment to alleviate chronic symptoms in CHIKV patients [ 17 , 118 120 ] including a randomized controlled trial [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it promotes bone and cartilage degradation. The balance between Th17/Treg plays an essential role in RA because Foxp3+ Treg cells help in inhibiting autoimmunity and immune tolerance [57,68]. In RA FLS, the hexokinase 2 (HK2) overexpression induces the level of MMP, IL-6.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Among them, the role of metabolism disruption has been basically confirmed. 3 Although the exact mechanism is still largely a mystery, it is undoubted that materials and energy generated by metabolism are required by immune functions. 4 , 5 Hence, it is not surprising to find that cell differentiation is always synchronized with metabolic reprogramming, and many metabolic regulators have been identified as the keys deciding phenotypes of immune cells.…”
Section: Introductionmentioning
confidence: 99%